Research of microstructure of the deposited composition 100X8+110G13 - Boyko, I. A.; Pashinskiy, V. V.; Pashinska, O. G.; Бойко, І. А.; Пашинський, В. В.; Пашинська, О. Г. (International Scientific Unity, 2025)
The results allow us to draw the following conclusions: 1. The proposed chemical composition of the Fe6 electrode meets the requirements of EN14700 and ensures the formation of a transition layer with a homogeneous dispersed structure when surfacing 110G13L steel parts without the formation of any excess phases and harmful non-metallic inclusions. This structure is favorable in terms of preventing the formation of cracks and delaminations of the deposited metal. 2. In the used surfacing mode, the influence of the base metal on the chemical composition of the deposited metal is observed only after the first pass. During subsequent passes, the properties of the deposited layer are determined by the material of the developed Fe6 electrode. 3. Further research should be aimed at determining the performance characteristics of the deposited layer.